2020 IEEE European Test Symposium (ETS) 2020
DOI: 10.1109/ets48528.2020.9131583
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Static Noise Margin for FinFET based SRAM PUFs

Abstract: In this paper, we develop an analytical PUF model based on a compact FinFET transistor model that calculates the PUF stability (i.e. PUF static noise margin (PSNM)) for FinFET based SRAMs. The model enables a quick design space exploration and may be used to identify critical parameters that affect the PSNM. The analytical model is validated with SPICE simulations. In our experiments, we analyze the impact of process variation, technology, and temperature on the PSNM. The results show that the analytical model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The WCHD slightly decreases when the technology is scaled. Note that for smaller nodes the impact 1190 Design, Automation and Test in Europe Conference (DATE 2022) of process variation is larger and hence, more cells get a larger asymmetry; this results in more predictable startup values [18]. The slight variations in WCHD can be attributed to process variation and different noise levels in the different technologies.…”
Section: B Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WCHD slightly decreases when the technology is scaled. Note that for smaller nodes the impact 1190 Design, Automation and Test in Europe Conference (DATE 2022) of process variation is larger and hence, more cells get a larger asymmetry; this results in more predictable startup values [18]. The slight variations in WCHD can be attributed to process variation and different noise levels in the different technologies.…”
Section: B Simulation Resultsmentioning
confidence: 99%
“…The WCHD analysis for both of them shows that the error in different conditions is less than the acceptable ECC capacity. In [18], the authors showed that the impact of temperature on static behavior of HP SRAM PUFs is higher than LP SRAM PUFs. In this work we have shown this subsequently leads to less noise in high-performance SRAM PUFs as compared to LP SRAM PUFs.…”
Section: Discussionmentioning
confidence: 99%
“…Highperformance SRAM PUF designs exhibit significantly reduced Hamming distance, ranging from 1 to 3 percent, in contrast to the 6 to 12 percent found in low-performance (LP) designs [13]. However, in [14], the authors showed that the impact of temperature on static behavior of HP SRAM PUFs is higher than LP SRAM PUFs.…”
Section: Existing Literature: Sram Puf Reliabilitymentioning
confidence: 97%
“…Usually, manufacturers introduce different kinds of packaging to trade-off among cost, noise immunity, and supporting different operating conditions [51]. • Aging: Usually, the SRAM signature (PUF) can be characterized by P SN M noise (PUF SN M noise) [20], [52].…”
Section: A Sources Of Distinguishable Factorsmentioning
confidence: 99%